Pelatihan Penulisan Karya Ilmiah untuk Pengembangan Profesi Guru di Jakarta Timur - Nurpratiwi, Suci; Amaliyah, Amaliyah (Yumary: Jurnal Pengabdian kepada Masyarakat, 2024)
Purpose: The specific objective to be achieved in this service activity is to improve the abilities and skills of PAI teachers to write scientific papers. Research methodology: The method used to implement community service is Participatory Action Research (PAR) through dialogue, discussion, and question and answer, as well as mentoring at several stages of meetings for participants. Results: Assistance activities in creating scientific work for teachers are very much needed, especially for PAI teachers. This is based on the need for promotion/position and fulfillment of requirements as a professional teacher. Some of the obstacles teachers face in creating scientific work are limited time at school for teaching and other administrative tasks. The obstacle in implementing community service activities is that teachers still have difficulty writing written work because they are still not used to it, so there are not many scientific works that can be submitted to scientific journals. Limitation: Mengedepankan tema-tema tertentu dalam penulisan karya ilmiah, seperti penelitian pendidikan, inovasi pengajaran, atau studi kasus di lingkungan sekolah. Contribution: Assistance in writing scientific papers for teachers at MGMP PAI at the high school level in East Jakarta can be concluded as successful. All participants gave positive responses with the largest percentage, namely that service activities provided additional knowledge related to the preparation of scientific articles for teachers. The participants suggested that the activities could be carried out on an ongoing basis so that participants could improve their competence in teaching, research, and writing.